Meta-emotion-regulation: a conceptual framework for influencing emotion regulation behaviour - Kraft, Lorenz; Kizil, Jana; Lindenberg, Katajun (Cognition & emotion, 2025)
If the short-term effectiveness or long-term adaptivity of emotion regulation (ER) depends on the specific ER (covert or overt) behaviours that are executed, it is important to know how to influence those behaviours. Whereas ER refers to influencing emotions, meta-emotion-regulation (MER) refers to influencing ER behaviours. Instead of trying to close the gap between desired and perceived emotion (like ER), MER tries to close the gap between intended and actual ER behaviour. We show how the concept of MER extends previous ideas by focusing on the determinants of ER choice and behaviour. Furthermore, we propose a first collection of potential MER strategies that may help increase desirable and decrease undesirable ER behaviour (e.g. deliberate practice or stimulus control). We also call for a research programme of identifying and testing MER strategies through experimental manipulations of probable ER choice determinants like ER beliefs or motivation. This could lead to new and refined clinical interventions and treatments in the context of ER, for example, by creating precise interventions aimed at reducing maladaptive avoidance, rumination, aggressive or addictive behaviour.